The Effect of Time Budget Pressure And Audit Risk On Au-dit Quality With Auditor's Ethics as A Moderating Variable - Wijayanti Suparto, Ayu Mastuti; Veda Hardhanie, Argya (Green Publisher Indonesia, 2023)
Relevant and reliable financial statements are information characteristics that are important for stakeholders in making decisions. The public accounting profession is a profession of public trust. In order to support his professionalism as a public accountant, in carrying out his audit duties, the auditor should be guided by the Professional Standards of Public Accountants (SPAP) set by the Indonesian Institute of Accountants (IAI). The motivation of researchers to conduct this research is because audit quality is currently very important for companies and shareholders. After all, many of the audits carried out by Public Accounting Firms do not carry out audit procedures and do not carry out the auditor's ethics that should be in conducting audits so that users of financial statements do not trust them. This study uses quantitative data with survey research. The results show that Time Budget Pressure has an effect on Audit Quality with Auditor Ethics as a moderating variable, while Audit Risk has no effect on audit quality with Auditor Ethics as a moderating variable.